FORMULASI DAN UJIANTIINFLAMASI SALEP EKSTRAK RESIN JERNANG (Daemonorops Draco (Wild)) Blume PADA MENCIT JANTAN PUTIH(Wistar). - Mayasari, Feliza; Novia, Devi; Yanuarto, Tri (Akademi Farmasi Yarsi Pontianak, 2025)
Jernang sap (Daemonorops draco (Willd.) Blume) is the exudate of the jernang rattan fruit which has been traditionally used as a traditional medicine. The active compounds contained in it include flavonoids, saponins, terpenoids, alkaloids, and phenolics, which are known to have potential as anti-inflammatory agents. This study aims to design a topical preparation in the form of an ointment from jernang sap extract and to test its physical quality and anti-inflammatory effects in vivo. The extraction process was carried out using a maceration technique using 96% ethanol, then the extract obtained was formulated into three variations of ointment with different concentrations (F1: 1%, F2: 2%, F3: 3%), using a base of vaseline flavum, lanolin, and propyl paraben as a preservative. Testing the physical quality of the ointment included organoleptic examination, homogeneity, pH value, spreadability, and viscosity. Anti-inflammatory activity was tested using male mice (Mus musculus) induced with 1% carrageenan on the paws, and the edema volume was measured using a plethysmometer. The results showed that an ointment made from jernang extract could be prepared with stable physical properties during storage. ANOVA analysis and further testing showed that formulas with higher concentrations (F2 and F3) provided a significant inflammation-inhibiting effect, nearly comparable to the positive control, a 2.5% hydrocortisone ointment. Thus, jernang extract has potential as a natural ingredient for topical anti-inflammatory ointments.